Strategi Kua Dalam Menanggulangi Pernikahan Dini Pada Remaja 15-18 Tahun : (Studi Pada Kabupaten Serdang Bedagai, Kecamatan Silinda) - Alfin Alfarihin; Muhammad Fachran Haikal (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to identify the strategies employed by the Silinda Subdistrict Office of Religious Affairs (KUA) to address early marriage among adolescents aged 15–18 years amid the ever-evolving dynamics of digital society and culture. Early marriage remains a social issue that impacts educational continuity, reproductive health, and family resilience, even though it is showing a downward trend nationally. This study employs a descriptive qualitative approach, using in-depth interviews and observation as data collection techniques. Research informants were selected through purposive sampling and included the head of the KUA, Islamic religious counselors, and KUA marriage officiants who are directly involved in policy formulation, the delivery of counseling, and the administrative processes of marriage. The results indicate that the KUA’s strategies are implemented through three main pillars. The educational pillar is realized through the School-Age Youth Guidance (BRUS) program and religious counseling that emphasizes psychological readiness, reproductive health, and an understanding of the ideal age for marriage. The administrative pillar is realized through the enforcement of marriage age regulations, the marriage registration system, and the mechanism for issuing marriage eligibility certificates. The collaborative pillar is carried out through cross-sectoral cooperation with schools, community health centers (Puskesmas), and local stakeholders. This study confirms that the effectiveness of early marriage prevention depends on the integration of religious education, administrative enforcement, and sustained institutional synergy